2020
DOI: 10.1002/jgc4.1285
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing costs and compliance with clinical best practices

Abstract: We sought to determine the costs of genetic testing and compliance with published guidelines and clinical best practices at our institution. A cost analysis was performed comparing the costs of ordered tests to the cost of the recommended testing. This was an approved quality improvement project at a tertiary teaching hospital in California. We identified charts associated with the genetic testing billing codes for common genetic tests through our contracted laboratory (cystic fibrosis genotyping, Breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Genetic counselors are trained to support the appropriate use of genetic testing (‘Practice‐Based Competencies’, 2019). Several studies have demonstrated the financial benefit of having genetic counselors review genetic testing orders for appropriateness (Miller et al., 2014; Montanez et al., 2020; Riley et al., 2015). With a majority of genetic testing being ordered by providers outside of genetics, the integration of genetic counselors into non‐genetics clinics is likely to expand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic counselors are trained to support the appropriate use of genetic testing (‘Practice‐Based Competencies’, 2019). Several studies have demonstrated the financial benefit of having genetic counselors review genetic testing orders for appropriateness (Miller et al., 2014; Montanez et al., 2020; Riley et al., 2015). With a majority of genetic testing being ordered by providers outside of genetics, the integration of genetic counselors into non‐genetics clinics is likely to expand.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing utilization of genetic testing across many conditions outside of rare genetic syndromes, the vast majority of patients are encountering genetic testing outside of a visit with a medical geneticist. There is also a growing shortage of genetics providers in health care, which may contribute to other specialists taking on conversations regarding genetic testing with their patients (Maiese et al, 2019) (Miller et al, 2014;Montanez et al, 2020;Riley et al, 2015). With a majority of genetic testing being ordered by providers outside of genetics, the integration of genetic counselors into non-genetics clinics is likely to expand.…”
Section: Ta B L E 3 Approved and Denied Test Requests By Testing Cate...mentioning
confidence: 99%
“…Insurance preauthorization is commonly required by payers for genetic tests to help eliminate excessive spending and misordering or outright fraud. Preauthorization enables insurance companies to decide how necessary a medical treatment is so they can deny the procedure/test/care before the service is provided, by reviewing the paperwork from the health care facility 104,105 . Industry partners on the coasts and well‐funded academic centers also have support staff to maximize payer reimbursement by means of the onerous preauthorization approval process, whereas small community health care facilities do not have sufficient staff or resources 106–108 .…”
Section: What Makes Molecular Pathology Susceptible To Unjust Distrib...mentioning
confidence: 99%
“…Author details 1 Department of Biomedical Informatics and Medical Education, School of Medicine, University of Washington, Seattle, WA, USA. 2 Institute of Translational Health Sciences, University of Washington, Seattle, WA, USA. 3 Department of Medicine (Medical Genetics), University of Washington, Seattle, WA, USA.…”
Section: Availability and Requirementsmentioning
confidence: 99%
“…Genetic testing is an essential tool to assist patients and clinicians to better understand the risk of hereditary disease. The cost of genetic testing has decreased and the number of genes routinely evaluated has increased in recent years, due to massively parallel sequencing methods and new discoveries [1,2]. Patients now have increased access to genetic information that can be important for their and their family's health.…”
Section: Introductionmentioning
confidence: 99%